Magnet Nanokomposit Sebagai Magnet Permanen Masa Depan [Nanocomposite Magnets as Future Permanent Magnets] - Idayanti, Novrita; Manaf, Azwar; Dedi (Jurnal Metalurgi, 2018)
This paper reviews research and development of permanent magnet materials based on study literatures that have been conducted by researchers in more than 100 years. It is known that the era of modern permanent magnets began in the early 19th century and lasted for approximately 100 years. In the past 100 years, it turned out the research focus of the researchers was to look for potential magnetic compounds. Not surprisingly, in a period of 100 years that various types of magnetic compounds were found. The rare earth metal magnet Nd-Fe-B was found at the end of the 19th century with a maximum energy product value or (BH)max of 56 MGOe (448 kJ.m-3) obtained. The value is the highest value ever achieved by researchers to date. However, the authors observe that since the early 20th century, there has been a change in the focus of research development that is currently not focus on the search and discovery of new magnetic phases, but rather to develop the magnetic material structure through the incorporation of hard magnetic phases with high magnetocrystalline value with a soft magnetic phase that has a high saturated magnetization value in a composite structure to become a nanocomposite magnets. The nanocomposite magnets are permanent magnets with superior magnetism properties compared to conventional magnets. The excellence magnetic properties are the value of remanent magnetization (Mr) and the maximum energy product (BH)max due to the effect of exchange coupled spring between the hard and soft magnetic phases so as to align the magnetic orientation of the two magnetic phases under the influence of exchange interaction. The theoretical researchers have also explored the potential of a nanocomposite permanent magnet and assigned (BH)max value of 1 MJ.m-3 as the ultimate value that must be achieved experimentally. The ultimate value has opened big challenges and become a new destination for experimental researchers. In this review paper, we present knowledge, research, and methods on improving the magnetism properties of ferrite, rare earth, and alloy metals based on exchange interaction mechanisms during the exchange spring magnet between hard and soft phases.